2012
DOI: 10.1080/01495739.2012.674830
|View full text |Cite
|
Sign up to set email alerts
|

Final Shape of Precision Molded Optics: Part I—Computational Approach, Material Definitions and the Effect of Lens Shape

Abstract: Coupled thermomechanical finite element models were developed in ABAQUS to simulate the precision glass lens molding process, including the stages of heating, soaking, pressing, cooling and release. The aim of the models was the prediction of the deviation of the final lens profile from that of the mold, which was accomplished to within one-half of a micron. The molding glass was modeled as viscoelastic in shear and volume using an n-term, prony series; temperature dependence of the material behavior was taken… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
48
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 44 publications
(51 citation statements)
references
References 22 publications
0
48
0
Order By: Relevance
“…The large deviations near the center and the edge of the lens are due to the cooling-induced shrinkage and edge effect, respectively [40]. For a precision lens, the allowed center thickness change is about 25 mm [41], and the maximum deviation of overall surface shape should be within several micrometers or smaller [77,78]. Thus, the above numerical analysis [40] has demonstrated that mold compensation is essential; otherwise the lenses by PGM are not usable.…”
Section: Mechanisms Of Lens Distortionmentioning
confidence: 99%
See 4 more Smart Citations
“…The large deviations near the center and the edge of the lens are due to the cooling-induced shrinkage and edge effect, respectively [40]. For a precision lens, the allowed center thickness change is about 25 mm [41], and the maximum deviation of overall surface shape should be within several micrometers or smaller [77,78]. Thus, the above numerical analysis [40] has demonstrated that mold compensation is essential; otherwise the lenses by PGM are not usable.…”
Section: Mechanisms Of Lens Distortionmentioning
confidence: 99%
“…Recently, a method was proposed for identifying the shear relaxation modulus and the structural relaxation function via measuring the time variation of the glass plate thickness [80]. The CTE variation was often modeled by the ToolNarayanaswamy-Moynihan (TNM) model [77,78], the parameterization of which needs structure relaxation tests and thermal expansion tests. It is clearly complicated to establish a constitutive model using these methods.…”
Section: Constitutive Modeling Of Optical Glassmentioning
confidence: 99%
See 3 more Smart Citations